Penguatan Ekonomi Masyarakat Pesisir Melalui Kolaborasi CSR Internasional: Penelitian - Mulyadi; Ervansyah Putra; Nuril Baeti; Ade Riska Febriani; Nursa’adah; Salmiyati; Yuslina; Senny Thirtywani; Nur’ain; Adhim Rafianto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The Coastal Community Economic Empowerment Program through International CSR Collaboration is a collaborative initiative between Ibnu Sina University Batam and Universiti Malaysia Terengganu (UMT) that aims to strengthen the coastal community economy through capacity building, technology transfer, and institutional strengthening based on international collaboration. Activities are carried out through workshops, technical training, hands-on training, benchmarking, and FGDs that focus on sustainable fisheries technology, modern mariculture, seafood processing, coastal business management, digital marketing strategies, and environmental conservation. Pre-test and post-test-based evaluations show significant improvements in three main aspects, namely coastal technical knowledge (±40%), business management capacity (±40%), and environmental awareness (±35%). In addition to improving participant competency, this program also broadens understanding of international CSR best practices and encourages the formation of action plans that can be replicated in Indonesian coastal communities. Overall, this activity has had a real impact on increasing the economic independence of coastal communities and has become an international CSR model with the potential for wider application..